2018
DOI: 10.32827/ijphcs.5.5.57
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Among Nurses in Primary Healthcare Clinics in the Health District of Petaling, Selangor

Abstract: Background: Quality of life (QOL) can influence the productivity of organization employees. In healthcare, commitment towards patient care depends greatly on the QOL of nurses. This study aims to determine QOL among nurses and its associated factors. Materials and Methods: A total of 322 nurses in the government healthcare clinics under the health district of Petaling participated in this cross-sectional study. The validated Malay version of WHOQOL-BREF questionnaire was used. Scores of the QOL domains were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The high QoL of the social health domain observed in the present study re ects participants' high level of contentment with social support and peer interaction in their daily lives. This is in agreement with a study in Malaysia which also observed the highest QoL scores in the social health domain among nurses [51].…”
Section: Discussionsupporting
confidence: 93%
“…The high QoL of the social health domain observed in the present study re ects participants' high level of contentment with social support and peer interaction in their daily lives. This is in agreement with a study in Malaysia which also observed the highest QoL scores in the social health domain among nurses [51].…”
Section: Discussionsupporting
confidence: 93%